Molecular Authentication of Twelve Meat Species Through a Promising Two-Tube Hexaplex Polymerase Chain Reaction Technique - Cai, Zhendong; Zhong, Guowei; Liu, Qianqian; Yang, Xingqiao; Zhang, Xiaoxia; Zhou, Song; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong (Frontiers in Nutrition, 2022)
Frequent meat frauds have aroused significant social attention. The aim of this study is to construct a two-tube hexaplex PCR method offering accurate molecular authentication of twelve meat species in actual adulteration event. DNA sequencing demonstrates that our designed primers can specifically amplify target species from genomic DNA mixture of six species in each tube reaction, which showed 100% accuracy of horse (148 bp), pigeon (218 bp), camel (283 bp), rabbit (370 bp), ostrich (536 bp) and beef (610 bp) as well as turkey (124 bp), dog (149 bp), chicken (196 bp), duck (277 bp), cat (380 bp) and goose (468 bp). Species-specific primer pair produced the target band in the presence of target genomic DNA but not nontarget species. Through multiplex PCR assays with serial concentration of DNA mixture of six species in each PCR reaction, the detection limit (LOD) of the two-tube hexaplex PCR assay reached to 0.05-0.1 ng. Using genomic DNA isolated from both boiled and microwave-cooked meat as the templates, PCR amplification generated the expected PCR products. All the findings demonstrate that the proposed method is specific, sensitive and reproducible, and is adequate for food inspection. Most importantly, this method has successfully applied to detect meat frauds in commercial meat products. Therefore, this method is of great importance with a good application foreground.